Modal analysis of plate-like cellular objects with periodic structure - V. V. Naprasnikov; A. V. Borodulya; Yu. V. Polozkov; D. P. Kunkevich; Tzu Zhui Wang (Системный анализ и прикладная информатика, 2024)
The method used to calculate natural frequencies and vibration shapes is described. Code fragments for construction for some types of filler are presented. The obtained frequencies and shapes of natural vibrations for three types of filler on the example of one construction are given.